ANALYSIS OF PUBLIC INTEREST IN ONLINE TOURISM IN THE MIDDLE OF THE COVID-19 PANDEMIC - Sugeng Santoso; Putri Aprilita Hapsari; Garys Difoasih; Susilo Edi Prianto (Universitas Terbuka, 2021)
This study aims to analyze people's interest in traveling in the era of the Covid-19 pandemic, with a focus on online tourism as an alternative to overcoming concerns about exposure to the virus and the imposition of Large-Scale Social Restrictions and Micro and Community- Scale Social Restrictions. The economic downturn in the midst of the threat of the spread of the pandemic which is not yet known when it will end, is a challenge for the government and society to adjust to the existing conditions. Currently, economic activities are re-opening by implementing health protocols to prevent and control the spread of the virus. It is necessary to restore tourists' trust in the midst of anxiety and the need to travel. This study used a qualitative descriptive research design with a cross sectional approach. Through an analysis of people' s interest in traveling in the era of the Covid-19 pandemic, it was found that the community (local tourists) had quite a high interest in online tourism. This is because the community assesses the urgency of fulfilling tourism needs during the Covid-19 pandemic, of course by paying attention to applicable health protocols. In the future, online tourism needs to be developed and introduced to the wider community, of course, judging by the magnitude of tourist attraction and the importance of restoring Indonesian tourism after the Covid-19 pandemic. Furthermore, further research needs to be carried out whether the development of online tourism based on technology and digital platforms will affect tourist visits directly to recreational areas and the implications for commodity transportation service providers or travel agents.